Quantification of blue carbon pathways contributing to negative feedback on climate change following glacier retreat in West Antarctic fjords - Zwerschke, Nadescha (Global change biology, 2022)
© 2021 The Authors. Global Change Biology published by John Wiley & Sons Ltd.